Head posture influences the geometric and hemodynamic features on the healthy human carotid bifurcation - Aristokleous, Nicolas; Khozeymeh, Mohammad Iman; Anayiotos, Andreas (My University, 2012)
Atherosclerosis is the third leading cause of morbidity and mortality in the Western world. Low and oscillating wall shear stress (WSS) regions have been previously reported as parameters that correlate with the development of atherosclerosis. In this study we investigated geometric and hemodynamic changes in the carotid bifurcation as a result of posture change. Data from magnetic resonance imaging (MRI) were used to construct three dimensional (3D) surface models and computational fluid dynamic (CFD) fields. Two healthy volunteers were imaged by MRI in three different head postures: a) the supine neutral (N) head position, b) the prone position with leftward head rotation (LR) up to 80° and c) the prone position with rightward head rotation (RR) up to 80o. The area exposure to unfavorable hemodynamics, based on thresholds set for oscillatory shear index (OSI), WSS and relative residence times (RRT), was used to quantify the hemodynamic impact on the wall. Significant change in the hemodynamic burden on the wall was found for the OSI. The velocity profile at the common carotid artery (CCA) upstream of the carotid bifurcation (CB) was investigated at the supine and RR prone position for six healthy volunteers. The results indicated that blood flow rate decreased at peak systole, for the prone position for both the right and left CCAs.
Keywords: Atherosclerosis; Hemodynamics; Carotid artery; Magnetic resonance imaging